Andexanet alfa - what we know about this promising drug - Ilnicka, Natalia; Zuziak, Patrycja; Sadlik, Maria; Matyja, Daria; Abod, Leila (Journal of Education, Health and Sport, 2023)
Introduction and purpose. Andexanet alfa (AA) is a recombinant modified version of human activated factor X. It is used as an antidote for apixsaban and rivaroxaban when reversal of anticoagulation due to life-threatening or uncontrolled bleeding is necessary. The aim of this paper is to present AA’s characteristics, treatment costs, clinical trial outcomes, and its use in medicine. Material and methods. A review of the available literature was performed by searching the PubMed and GoogleScholar databases using the following keywords: “andexanet alfa”, “factor Xa inhibitors”, “anticoagulant reversal”. Literature analysis. AA sequesters factor Xa inhibitors, which reactivates the endogenous factor Xa and reverses the anticoagulant effect. It is well tolerated, with a rapid onset of action. Side effects such as pneumonia, urinary tract infections and augmented thromboembolic risk have been observed. There are two dosing regimens, dependant on the ingested anticoagulant dose. Single dose cost is as high as 30 or 60 thousand USD. Conclusion. AA represents a therapeutic advancement and can prove life-saving in patients who experience an acute major bleeding while treated with direct oral anticoagulants. Single dose cost is high, therefore its availability for use may be restricted.